Serum C-Reactive Protein and Periodontitis: A Systematic Review and Meta-Analysis - Machado, Vanessa; Botelho, João; Escalda, Cláudia; Hussain, Syed Basit; Luthra, Shailly; Mascarenhas, Paulo; Orlandi, Marco; Mendes, José João; D’Aiuto, Francesco (Frontiers in Immunology, 2021)
Periodontitis has been associated with low-grade inflammation as assessed by C-reactive protein (CRP) levels and its treatment can decrease CRP serum levels. The aim of this systematic review was to critically appraise the evidence comparing CRP serum levels (standard and high-sensitivity [hs]) of otherwise healthy patients suffering from periodontitis when compared to controls. The impact of intensive and non-intensive nonsurgical periodontal treatment (NSPT) on hs-CRP was also investigated. Four electronic databases (Pubmed, The Cochrane Central Register of Controlled Trials [CENTRAL], EMBASE and Web of Science) were searched up to February 2021 and the review was completed according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines (PROSPERO No. CRD42020167454). Observational and intervention studies that: 1) evaluated CRP and hs-CRP serum levels in patients with and without periodontitis, and; 2) hs- CRP levels after NSPT were included. Following risk of bias appraisal, both qualitative and quantitative analyses were performed. Pooled estimates were rendered through ratio of means (RoM) random-effects meta-analyses. After screening 485 studies, 77 case-control studies and 67 intervention trials were included. Chronic and aggressive periodontitis diagnoses were consistently associated with higher levels of CRP and hs-CRP (p<0.001). Patients with aggressive periodontitis exhibited on average more than 50% higher levels of CRP (RoM [95% confidence interval [CI]]: 1.56 [1.15; 2.12], p=0.0039) than patients with chronic periodontitis. Intensive NSPT induced an immediate increase of hs-CRP followed by a progressive decrease whilst non-intensive NSPT consistently decreased hs-CRP after treatment up to 180 days (p<0.001). These findings provide robust evidence that periodontitis is associated with systemic inflammation as measured by serum CRP levels. Periodontitis treatment induces a short-term acute inflammatory increase when performed in an intensive session, whilst a progressive reduction up to 6 months was demonstrated when performed in multiple visits.